De la machine de la fête baroque à la performance urbaine : éphémère éternel - Alessandra Cirafici (Ambiances)
The contribution aims to investigate the historical origins of the phenomenon defined as “ephemeral architecture” that was first developed in the baroque Rome of Bernini and found its own expressive nature in the culture and language that made the Neapolitan baroque great, through the likes of Cosimo Fanzago, Ferdinando San Felice and Domenico Antonio Vaccaro. However, starting from a study of the significance that the macchina della festa barocca had on the urban development of the city, in defining the collective spaces and on the founding of the idea of the piazza, it will be possible to consider in a more general sense the power of renewal and persuasion that the provisional is capable of promoting in the life of cities over time, as well as on the role that the ephemeral, intended as an anthropological category, has had and continues to have on the development and definition of the concept of an urban space that is defined and measured through its rituals of use, its performances, the deep sense of wonder, amazement and participation that the ephemeral brings with it.